Dielectric dispersion and superior thermal characteristics in isotope-enriched hexagonal boron nitride thin films: evaluation as thermally self-dissipating dielectrics for GaN transistors. Issue 28 (26th June 2020) - Chng, Soon Siang; Zhu, Minmin; Du, Zehui; Wang, Xizu; Whiteside, Matthew; Ng, Zhi Kai; Shakerzadeh, Maziar; Tsang, Siu Hon; Teo, Edwin Hang Tong
Abstract : The isotope-enriched h-BN films exhibited a dielectrics dispersion with low dielectric loss, below 1.3%. Their optical band gaps depend on isotopic composition (5.54 to 5.79 eV). Thermal conductivity of pure B 10/11 N are enhanced by around 231%. Abstract : High performance tuneable dielectrics at millimetre-wave frequencies are crucial constituents for emerging adaptive and reconfigurable electronic applications in the automotive, artificial intelligence, and telecommunication industries. Hexagonal boron nitride (h-BN), an ideal candidate for gate-insulating dielectrics, is attractive for integrated circuits and photonic devices. However, advanced application to electronic and optoelectronic devices has often been limited by synthesis techniques and flake size, as well as dielectric reliability. Herein, we have studied the isotope engineering of h-BN thin films directly grown on wafer-scale Si and GaN substrates with pure boron isotopes (B 10 and B 11 ) in comparison with controlled isotopic compositions. The dielectric characteristics of isotope-enriched h-BN films at frequencies ranging up to 10 7 Hz were investigated, exhibiting a broad dielectric dispersion with a low dielectric loss, below 1.3%. Furthermore, their optical band gap energies indicate a strong dependence on isotopic composition, ranging from 5.54 to 5.79 eV. Thermal conductivity of pure B 10 N and B 11 N over a broad temperature range is superior to those of other compositions, with an enhancement of around 231%. Therefore, the great thermal response combined with excellent dielectric properties and a wide band gap make h-BN a promising dielectric material for heat self-dissipating GaN and AlGaN /GaN transistors. Hall mobility, sheet resistivity and sheet concentration of GaN with B 10 N films were analyzed, ascertaining that h-BN does function well as both a dielectric layer and a passivating layer on electronic devices. Our findings could lead to microelectronics thermal management and integrated optoelectronic applications at these frequencies.